Heliospheric Structure Analyzer (HSA): A Simple 1-AU Mission Concept Focusing on Large-Geometric-Factor Measurements - Borovsky, Joseph E.; Raines, Jim M. (Frontiers in Astronomy and Space Sciences, 2022)
To obtain measurements that will address some outstanding questions about the properties and origin of the magnetic and plasma structure of the heliosphere a simple single-spacecraft mission at 1 AU is outlined. By focusing on large-geometric-factor measurements of particles (protons, alphas, heavy ions, and electrons) several longstanding questions can be answered. The key objectives of the large-geometric-factor measurements are lower noise and faster time resolution. Much of the focus is on critical measurements associated with the ubiquitous current sheets (directional discontinuities) of the solar wind that provide information about the origin and evolution of the current sheets and about the origin and evolution of the magnetic and plasma structures that they define.